2019
DOI: 10.1109/access.2019.2960629
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Spontaneous Micro-Expression Using a Three-Stream Convolutional Neural Network

Abstract: Micro-expression recognition (MER) has attracted much attention with various practical applications, particularly in clinical diagnosis and interrogations. In this paper, we propose a three-stream convolutional neural network (TSCNN) to recognize MEs by learning ME-discriminative features in three key frames of ME videos. We design a dynamic-temporal stream, static-spatial stream, and local-spatial stream module for the TSCNN that respectively attempt to learn and integrate temporal, entire facial region, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 77 publications
0
73
0
Order By: Relevance
“…This work will contribute to the further exploration of sparse binary descriptors, which will improve the prediction of MEs, and thus combining the advantages of handcrafted features with deep learning technology will be our future work. ELBPTOP * [42] Extended Local Binary Patterns on Three Orthogonal Planes Bi-WOOF+Phase * [43] Bi-Weighted Oriented Optical Flow with phase information ELRCN * [24] Enriched Long-term Recurrent Convolutional Network 3D flow-based CNN * [26] 3D flow-based convolutional neural networks TSCNN * [28] Transferring Long-term Convolutional Neural Network SSSN * [44] Single-Stream Shallow Network DSSN * [44] Dual-Stream Shallow Network…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This work will contribute to the further exploration of sparse binary descriptors, which will improve the prediction of MEs, and thus combining the advantages of handcrafted features with deep learning technology will be our future work. ELBPTOP * [42] Extended Local Binary Patterns on Three Orthogonal Planes Bi-WOOF+Phase * [43] Bi-Weighted Oriented Optical Flow with phase information ELRCN * [24] Enriched Long-term Recurrent Convolutional Network 3D flow-based CNN * [26] 3D flow-based convolutional neural networks TSCNN * [28] Transferring Long-term Convolutional Neural Network SSSN * [44] Single-Stream Shallow Network DSSN * [44] Dual-Stream Shallow Network…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [27] proposed a cascade structure of three VGG-NETs and a Long Short-Term Memory (LSTM) network LSTM, and integrated three different attention models in the spatial-domain. Song et al [28] developed a Three-stream Convolutional Neural Network (TSCNN) by encoding the discriminative representations in three key frames. TSCNN consisted of a dynamic-temporal stream, static-spatial stream, and local-spatial stream module, which are used to capture the characteristics of temporal, entire facial region, and local facial region, respectively.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The method had been proposed with application to facial expression recognition and reported over 95% accuracy. Moreover, a recent study on spontaneous facial micro-expression recognition suggested a deep learning model based on spatial and temporal streams and reported 63.53–74.05% accuracy [ 21 ].…”
Section: Related Workmentioning
confidence: 99%